Seed dispersal limitation causes negative legacy effect on restoration of grassland plant diversity on ski slopes - Yuki A. Yaida; Taiki Inoue; Tanaka Kenta; Atushi Ushimaru (Ecology and Evolution)
Abstract Past forest use often has a long‐term negative impact on the recovery of the original plant composition of semi‐natural grasslands, which is known as a legacy effect. This study investigates the impact of seed dispersal limitations on the restoration of grassland plant diversity on ski slopes with past forest use, highlighting the negative legacy effect on biodiversity recovery. Focusing on ski areas, our research contrasts the vegetation on ski slopes originally created on semi‐natural grasslands such as pasture (pasture slopes) and constructed by clearing secondary forests or conifer plantations (forest slopes). We examined species richness and diversity, considering seed dispersal modes, grassland management history, and seed source proximity. We reveal that the proximity to species‐rich grassland sources is pivotal for the restoration of native grassland vegetation. Particularly, wind‐dispersed species show significant recovery on slopes with sustained management for more than 70 years and those with neighboring species‐rich grasslands, suggesting that both the duration of management and the proximity to seed sources are critical for overcoming the legacy effects of past forest use. Meanwhile, gravity‐dispersed species failed to recover their richness and diversity regardless of both the duration of management and the proximity to seed source grasslands, which their diversity recovered where seed sources neighbored. Our findings emphasize the importance of considering seed dispersal limitation and management history in the restoration and conservation of grasslands and their biodiversity, particularly in landscapes experiencing past human intervention.